2018
DOI: 10.1016/j.micres.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a new Bacillus atrophaeus strain B5 as biocontrol agent of postharvest anthracnose disease in soursop (Annona muricata) and avocado (Persea americana)

Abstract: Anthracnose is a fungal disease caused by Colletotrichum species that is detrimental to numerous fruit, including soursop and avocado. The use of fungicides to maintain the high quality of fruit creates a potential health risk. One alternative to this problem is the biological control, which has been applied successfully during postharvest. The Bacillus species are one of the most studied biological agents against postharvest pathogens because accomplish their biocontrol performance by producing a variety of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 38 publications
0
31
0
1
Order By: Relevance
“…and rhizosphere of wheat, respectively. These two sites were selected to fit the definable environmental limits for the existence of the biological control agent (Debbi et al, 2018; Gomez-Lama Cabanas et al, 2018; Guardado-Valdivia et al, 2018). More than 140 bacterial isolates were recovered from these two sites and screened for their inhibitory effect against F. oxysporum f. sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and rhizosphere of wheat, respectively. These two sites were selected to fit the definable environmental limits for the existence of the biological control agent (Debbi et al, 2018; Gomez-Lama Cabanas et al, 2018; Guardado-Valdivia et al, 2018). More than 140 bacterial isolates were recovered from these two sites and screened for their inhibitory effect against F. oxysporum f. sp.…”
Section: Discussionmentioning
confidence: 99%
“…Biological control relies on screening for pest or pathogen antagonists or natural enemies, originating from its area of spread or areas that closely match the climate and soil type of the infested region by the pest or pathogen. This allows researchers to match the definable environmental limits for the existence of the biological control agent (Debbi et al, 2018; Gomez-Lama Cabanas et al, 2018; Guardado-Valdivia et al, 2018). Despite the selection of definable environmental limits for the existence of the biological control agent, some biocontrol agents fail to compete or colonize the rhizosphere of inoculated plants (Mefteh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that iturinic lipopeptides possess strong antifungal activity (Mhammedi et al, 1982; Peypoux et al, 1986; Ongena and Jacques, 2008; Ma et al, 2012; Guardado-Valdivia et al, 2018) and induce defense responses in plants (Farace et al, 2015; Park et al, 2016; Wu et al, 2018) which, in turn, has led to the commercialization of many Bacillus strains that manufacture these compounds (Dunlap, 2019). Interestingly, no known resistance mechanisms to iturinic lipopeptides have been reported in fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recently reported antifungal lipopeptides in B. atrophaeus , but none have identified the active compound (Zhang et al, 2013, 2016; Chen et al, 2017; Guardado-Valdivia et al, 2018). This study was first to identify B. atrophaeus as a producer of mycosubtilin.…”
Section: Discussionmentioning
confidence: 99%
“…is an economically important commodity for Mexican agriculture, as the country produces approximately 35% of the avocado global production [1]. However, the productivity of avocado orchards has been set back by the occurrence of fast-spreading diseases such as Phytophthora root rot, caused by the oomycete Phytophthora cinnamomi [2], or anthracnose, caused by Colletotrichum gloeosporioides [3]. Recently, two fungal diseases vectored by invasive ambrosia beetles have been hindering avocado production in the USA [4][5][6], in Israel [7], and have been newly reported in South Africa [8].…”
Section: Introductionmentioning
confidence: 99%